Scientific Basis of the Strategy of Holistic Sustainable Development of an Individual, Nation, Civilization - Suvorov, Nikolay; Suvorova, Irina (European Journal of Sustainable Development, 2019)
The twentieth century was full of many crises and crisis events in various areas of people’s lives. There were crises in science, in particular, physics. There were inter-ethnic, economic, political, financial, social crises, which entailed wars and revolutions. Politicians, sociologists explain, for various reasons and factors, the abundance of crises of the 20th century. But in essence, all crises were the result of the most important crisis of the spiritual, mental and moral crisis, the crisis of consciousness, the soul of an individual. The modern era is characterized by an ecological crisis, a crisis of culture, a crisis of generations of people, a crisis of upbringing, and many, many other crises. At present, all the crises brought mankind to the brink of nuclear and environmental catastrophes. The essence, causes of the emergence of a spiritual crisis, as well as ways out of it to form the scientific foundations of the strategy of holistic sustainable development of an individual, nation, and civilization are considered. Key words: harmony-peace, harmony-love, innovative, cardinal transformation, metamorphosis.